VARIABLES THAT AFFECT CONSUMER DECISION TO BUY MOBILE PHONE PRODUCT - Didin Mukodim; Erliansyah Erliansyah (Jurnal Ilmiah Ekonomi Bisnis, 2009)
Communication is an important aspect in human life that has significantly changes human life styles. Mobile phones are one of communication device that has been widely used by millions of people around the world, including Indonesia. This study is aimed analyzing variables which have the potentials to influence mobile phone consumer buying decision. Primary data covering variables such as subjective norms, company brand, level of information process, and consumers’ buying decision were used. Data were collected from respondents, who are mobile phone users, using questionnaires which have been tested (i.e., validity and reliability tests). Factor analysis along with multiple regression analysis was performed. Results of the study indicated that subjective norms and company brand were found as variables having stronger influences on mobile phone consumer buying decision.Key words: consumer buying decision; subjective norms; company brand; level of information process.